Exploring β-catenin and TCF4 interaction in complex environments by means of novel biosensing platform focal molography - Philipp Cedro; Roman Popov; Maxime Karrer; Jean-Christophe Hau; Eric-André Kusznir; Ralf Thoma; Andreas Frutiger; Matthias Lauer; Sylwia Huber (PLoS ONE, 2025)
Analyzing biomolecular interactions is essential for drug discovery, aiding the design of new candidates by revealing their action with targets. Various biophysical methods are routinely applied to characterize binding properties between molecules. Recently, focal molography, a novel sensor-based technology, has been developed to study interactions in complex environments. It measures changes in the intensity of diffracted light at a focal point due to analyte binding to a patterned array of binding sites, known as a mologram. Focal molography filters a specific binding signal from nonspecific background binding, allowing holistic analysis in biologically relevant environments. We present binding data and method’s validation in both, buffer and complex media, using focal molography and compare results to the gold standard method, surface plasmon resonance. Our model system focuses on the interaction between β-Catenin and a T-cell factor 4. β-Catenin, crucial in gene regulation for cell proliferation and differentiation, is a key target in cancer therapeutics. Confirming focal molography’s ability to accurately measure binding affinities creates a reliable methodology that fills gaps in current drug discovery techniques.